1998
DOI: 10.2307/3587999
|View full text |Cite
|
Sign up to set email alerts
|

The Alternatives in Language Assessment

Abstract: Language testing differs from testing in other content areas because language teachers have more choices to make. The purpose of this article is to help language teachers decide what types of language tests to use in their particular institutions and classrooms for their specific purposes. The various kinds of language assessments are classified into three broad categories: (a) selected‐response assessments (including true‐false, matching, and multiple‐choice assessments); (b) constructed‐response assessments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
202
0
25

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(230 citation statements)
references
References 45 publications
3
202
0
25
Order By: Relevance
“…They voiced their frustration over the issues of design decision, logistics and interpretation. They also challenged the portfolio assessment's time-consuming nature, and the issues of reliability and validity (Brown &Hudson 1998).…”
Section: Portfolio Assessmentmentioning
confidence: 99%
“…They voiced their frustration over the issues of design decision, logistics and interpretation. They also challenged the portfolio assessment's time-consuming nature, and the issues of reliability and validity (Brown &Hudson 1998).…”
Section: Portfolio Assessmentmentioning
confidence: 99%
“…Although it is preferable that feedback is given by the teacher, research has shown a number of advantages of selfcorrection and peer-assessment on speed, direct involvement of students, the encouragement of autonomy, and increased motivation because of selfinvolvement in the process of learning (Brown & Hudson, 1998, cf. Brown, 2001).…”
Section: Feedback On Teachingmentioning
confidence: 99%
“…According to Bayraktar (2009), oral conferencing is identified and "referred to as response sessions, assisted performance, face-to-face interaction, one-toone teaching, conversation about the student's paper, and meaningful contact" (p. 11). Oral conferencing is advantageous in a way that teachers can foster learners' reflection on their own learning process; elicit language performances on particular tasks, skills, or other language points as well as helping them to develop a better self-image (Brown & Hudson, 1998).…”
Section: Introductionmentioning
confidence: 99%